SEPTEM VERBA A CHRISTO W STAROPOLSKICH APOKRYFACH NOWOTESTAMENTALNYCH W PERSPEKTYWIE ŹRÓDŁOZNAWCZEJ I LINGWISTYCZNEJ. CZĘŚĆ PIERWSZA: ŹRÓDŁA - ZIÓŁKOWSKA, OLGA (Slavia Occidentalis, 2020)
This article is the first of two parts of a description of the motif of the seven words uttered by the crucified Christ in old Polish biblical and apocrypha narrations. The author presents the origin of the motif, characteristics of old Polish texts in which it occurred; the most important differences have been highlighted in the feature arrangement of the specific fragments of old Polish Passion of Jesus. The body of the article is represented by depiction of the sources of the seven words uttered by Christ on the cross, presentation of various ways of medieval scribes using the Holy Scriptures and an attempt to capture the motif severing itself from the original source. While the words uttered by Jesus on the cross come from the Gospels, neither of the four evangelists confirmed all of them. The chronology of the words is also arbitrary. In all old Polish apocrypha containing a description of Christ’s death on the cross, the motif of the seven words plays an important role and has been analysed with respect to the content and the vocabulary. The second part of the characteristics will be devoted to the linguistic development of the description of the motif in question.